Complications of preventive loop ileostomy versus colostomy: a meta-analysis, trial sequential analysis, and systematic review - Zheng Ge; Xiang Zhao; Zitian Liu; Guangwei Yang; Qunzheng Wu; Xiaoyang Wang; Xiang Zhang; Zhiqiang Cheng; Kexin Wang (BMC Surgery, 2023)
Abstract Background Preventive colostomy is required for colorectal surgery, and the incidence of complications associated with ileostomy and colostomy remains controversial. This study aimed to compare the incidence of postoperative complications between ileostomy and colostomy procedures. Methods Data analysis was conducted on 30 studies, and meta-analysis and trial sequential analysis (TSA) were performed on five studies. The basic indicators, such as stoma prolapse, leak, wound infection, ileus, and a series of other indicators, were compared. Results No statistically significant differences were observed with complications other than stoma prolapse. Meta-analysis and TSA showed that the incidence of ileostomy prolapse was lower than that of colostomy prolapse, and the difference was statistically significant. Apart from the four complications listed above, the general data analysis showed differences in incidence between the two groups. The incidence of skin irritation, parastomal hernia, dehydration, pneumonia, and urinary tract infections was higher with ileostomy than with colostomy. In contrast, the incidence of parastomal fistula, stenosis, hemorrhage, and enterocutaneous fistula was higher with colostomy than with ileostomy. Conclusions There were differences in the incidence of ileostomy and colostomy complications in the selected studies, with a low incidence of ileostomy prolapse. PROSPERO registration number CRD42022303133.